2022
DOI: 10.1002/jor.25363
|View full text |Cite
|
Sign up to set email alerts
|

Gait biomechanics phenotypes among total knee arthroplasty candidates by machine learning cluster analysis

Abstract: Knee osteoarthritis patient phenotyping is relevant to developing targeted treatments and assessing the treatment efficacy of total knee arthroplasty (TKA). This study aimed to identify clusters among TKA candidates based on demographic and knee mechanic features during gait, and compare gait changes between clusters postoperatively. TKA patients underwent 3D gait analysis 1‐week pre (n = 134) and 1‐year post‐TKA (n = 105). Principal component analysis was applied to frontal and sagittal knee angle and moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Phenotyping is an emerging field in orthopaedic research that offers a more nuanced understanding of patient heterogeneity and has the potential to guide management decisions (Nelson, 2018). While this study focused on PROMs, previous studies have stratified patients with OA can be stratified based on knee alignment, radiographic features, kinematics, metabolomics, and more (Dell'Isola, Allan, et al, 2016;Deveza et al, 2017;Dório & Deveza, 2022;Moser et al, 2020;Pan et al, 2020;Petersen et al, 2022;Young-Shand et al, 2023;Zhang et al, 2014). For instance, Moser et al (2020) identified diverse knee phenotypes based on knee alignment and recommended personalised TKA realignment for improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotyping is an emerging field in orthopaedic research that offers a more nuanced understanding of patient heterogeneity and has the potential to guide management decisions (Nelson, 2018). While this study focused on PROMs, previous studies have stratified patients with OA can be stratified based on knee alignment, radiographic features, kinematics, metabolomics, and more (Dell'Isola, Allan, et al, 2016;Deveza et al, 2017;Dório & Deveza, 2022;Moser et al, 2020;Pan et al, 2020;Petersen et al, 2022;Young-Shand et al, 2023;Zhang et al, 2014). For instance, Moser et al (2020) identified diverse knee phenotypes based on knee alignment and recommended personalised TKA realignment for improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years significant strides have been made in this direction. For instance, previous research has attempted to group patients with OA into phenotypes based on gait kinematics (Petersen et al, 2022; Young-Shand et al, 2023), joint aspirate metabolomics (Zhang et al, 2014), pain groups (Pan et al, 2020), functional knee characteristics (Moser et al, 2020), structural characteristics, and prognosis (Dell’Isola et al, 2016). Recent studies have found that phenotypes based on a combination of preoperative PROMs were associated with dissatisfaction after TKA and postoperative PROMs (Kung et al, 2023; Orr et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison investigation led them to the conclusion that an LR classifier trained on six weeks of post-operative biomechanical data during walking was responsive to changes at 3, 6, and 12 months post-TKA (with a 67.3% accuracy). In contrast with the other studies, Young-Shand et al identified clusters among TKA candidates and postoperatively using knee biomechanical parameters during gait and demographic data and machine learning cluster analysis [25]. They performed 3D gait analysis on 134 pre-and 105 post-TKA patients, and they used PCA as a feature reduction technique.…”
Section: Tka Surgerymentioning
confidence: 99%
“…The main inclusion criteria were knee OA and the wait time for total knee replacement. Young-Shand et al employed 135 subjects 1 week before and 109 subjects one year post-TKA with the main aim to determine clusters among TKA candidates and compare gait differences between clusters post-surgery [25]. The main inclusion criterion was the ability to walk 6 m without a walking aid.…”
Section: Subject Characteristicsmentioning
confidence: 99%